2020
DOI: 10.1029/2019ja027310
|View full text |Cite
|
Sign up to set email alerts
|

Arase Observation of the Source Region of Auroral Arcs and Diffuse Auroras in the Inner Magnetosphere

Abstract: Auroral arcs and diffuse auroras are common phenomena at high latitudes, though characteristics of their source plasma and fields have not been well understood. We report the first observation of fields and particles including their pitch‐angle distributions in the source region of auroral arcs and diffuse auroras, using data from the Arase satellite at L ~ 6.0–6.5. The auroral arcs appeared and expanded both poleward and equatorward at local midnight from ~0308 UT on 11 September 2018 at Nain (magnetic latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
0
11
2
Order By: Relevance
“…Using test particle simulations, Birn et al (2014) has demonstrated formation of the field-aligned distribution of thermal electrons (with energies of tens of keV down to sub-keV) through adiabatic acceleration associated with dipolarization fronts. Thus, we cannot rule out the contribution of adiabatic effects to the formation of field-aligned electrons in our event (see also Shiokawa et al, 2020).…”
Section: Geophysical Research Lettersmentioning
confidence: 93%
“…Using test particle simulations, Birn et al (2014) has demonstrated formation of the field-aligned distribution of thermal electrons (with energies of tens of keV down to sub-keV) through adiabatic acceleration associated with dipolarization fronts. Thus, we cannot rule out the contribution of adiabatic effects to the formation of field-aligned electrons in our event (see also Shiokawa et al, 2020).…”
Section: Geophysical Research Lettersmentioning
confidence: 93%
“…9 Faculty of Engineering, Kyushu Institute of Technology, 1-1 Sensui-cho, Tobata-ku, Kitakyushu, Fukuoka 804-8550, Japan. 10 Research Institute for Sustainable Humanosphere, Kyoto University, Gokasho, Uji, Kyoto 611-0011, Japan. * email: imajos@isee.nagoya-u.ac.jp A typical representation of the acceleration region observed by previous low altitude satellites is as follows 6 .…”
Section: Openmentioning
confidence: 99%
“…Such an acceleration region is assumed to lie in the transition region between ionospheric and magnetospheric plasmas, typically at 1000-20,000 km altitudes 1 . However, there have been several reports of signatures reminiscent of potential-driven acceleration above 20,000 km, outside the ionosphere-magnetosphere transition region [7][8][9][10] . It is unclear whether electrons accelerated from such high altitudes can precipitate to the ionosphere and excite auroral emissions, owing to the small loss cone in the region.…”
Section: Openmentioning
confidence: 99%
“…With the RBSP-B, they observed an upward field-aligned current (FAC) located within the tailward part of a spatially localized plasma pressure peak, suggesting the role of local pressure gradients as a driver for the upward FAC in the arcs. Shiokawa et al (2020) comprehensively analyzed the source region of auroral arcs during a substorm expansion phase using the Arase satellite at a geocentric distance of ∼5.8 R E and ∼−17° MLAT. They found strong electric field fluctuations with large earthward/tailward Poynting fluxes and bidirectional electrons that can be considered as earthward plasma injections through the Fermi-type electron acceleration at energies above a few keV and upward field-aligned potential difference at energies below a few keV.…”
mentioning
confidence: 99%